Journal of Cardiovascular Magnetic Resonance - Leiner, Tim.; Manning, Warren; SpringerLink (Online service) (London : BioMed Central : Imprint: BioMed Central.)
Journal of Cardiovascular Magnetic Resonance will cease to be published by BMC as of 31st December 2023. The journal will continue in cooperation with a new publisher. For new manuscript submissions, please visit https://www2.cloud.editorialmanager.com/jofcmr/default2.aspx. BMC will continue to host an archive of all articles previously published in the journal and all articles published in Journal of Cardiovascular Magnetic Resonance during its time with BMC will remain fully searchable via the BMC website. Journal of Cardiovascular Magnetic Resonance (JCMR) publishes high-quality articles on all aspects of basic, translational and clinical research on the design, development, manufacture, and evaluation of cardiovascular magnetic resonance (CMR) methods applied to the cardiovascular system. Topical areas include, but are not limited to: New applications of magnetic resonance to improve the diagnostic strategies, risk stratification, characterization and management of diseases affecting the cardiovascular system. New methods to enhance or accelerate image acquisition and data analysis. Results of multicenter, or larger single-center studies that provide insight into the utility of CMR. Basic biological perceptions derived by CMR methods.
Keywords: Imaging systems in biology; Blood-vessels$1 (BDiseases.s; Cardiology; Biological Imaging; Angiology; Cardiology